Reconstitution of Contractile Actomyosin Arrays - Murrell, Michael (Methods Enzymol, 2014)
Networks and bundles comprised of F-actin and myosin II generate contractile forces used to drive morphogenic processes in both muscle and nonmuscle cells. To elucidate the minimal requirements for contractility and the mechanisms underlying their contractility, model systems reconstituted from a known set of purified proteins in vitro are needed. Here, we describe two experimental protocols our lab has developed to reconstitute 1D bundles and quasi-2D networks of actomyosin that are amenable to quantitative biophysical measurement. These assays have enabled our discovery of the mechanisms of contractility in disordered actomyosin assemblies and of a mechanical feedback between contraction and F-actin severing.